Subclinical effects of adapalene‐benzoyl peroxide: a prospective in vivo imaging study on acne micromorphology and transfollicular delivery. (5th March 2021) - Fuchs, C.S.K.; Ortner, V.K.; Hansen, F.S.; Philipsen, P.A.; Haedersdal, M.
Abstract: Background: Adapalene–benzoyl peroxide (A‐BPO) is a first‐line topical treatment for acne vulgaris. In vivo reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) detect micromorphological changes over time and visualize transfollicular delivery. Objectives: To visualize temporal, subclinical effects of A‐BPO on acne micromorphology using RCM and OCT, and evaluate their impact on transfollicular delivery of microparticulate carrier systems. Methods: Fifteen patients with mild to moderate acne received a 6‐week course of A‐BPO. Micromorphological changes were evaluated at time 0, 3 and 6 weeks with RCM ( n  = 1190 images) and OCT ( n  = 210 scans). Transfollicular delivery of microparticles was assessed at baseline and week 6. Results: In vivo imaging visualized steady normalization of skin micromorphology in response to A‐BPO over 6 weeks, including decreased hyperkeratinization of follicular borders (RCM median decrease −71.2%, P  < 0.05), reduced intrafollicular keratinous content (RCM median decrease −47.7%, P  < 0.05) and increased epidermal thickness (OCT median increase of 25.25%, P  < 0.05). Imaging visualized microparticles in the follicular unit. Despite a visible reduction in keratin and sebum, transfollicular microparticle delivery appeared unaffected. Conclusions: Reflectance confocal microscopy and OCT detect A‐BPO‐induced changes in micromorphology and visualize transfollicular microparticle delivery. Keratolysis and sebolysis did not have a measurable effect on transfollicular delivery of microparticles.